2017
DOI: 10.1007/s00264-017-3444-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of anatomical plating systems for comminuted distal humeral fractures

Abstract: Purpose Six different mono-axial and poly-axial distal humeral plating systems with an anatomical plate design were compared. The aim of the biomechanical tests was to examine differences regarding system stiffness, median fatigue limit, and failure mechanisms. Methods Different configurations of two double plate fixation systems by two manufacturers for the treatment of complex distal humeral fractures (AO/OTA type C2.3) were biomechanically tested in a physiologically relevant setup. Results The 180°Stryker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Successful treatment for comminuted DHFs requires bicolumnar fixation with sufficient biomechanical stability [7,8] to allow early elbow range of motion and avoid post-operative complications such as non-union and implant failure [4][5][6]. Although several studies had found that parallel plating can provide good clinical results and is biomechanical superior to orthogonal plating in osteoporotic fracture [1,22], it is associated with a greater extent of soft tissue dissection in the distal humerus [11,12] a higher HO formation rate [23,24], and greater difficulty in contouring and applying the lateral plates [19]. Posterior two-plate fixation is considered to be an alternative technique [17] that also has good functional outcomes, high union rates, and low complication rates in c-type DHFs [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful treatment for comminuted DHFs requires bicolumnar fixation with sufficient biomechanical stability [7,8] to allow early elbow range of motion and avoid post-operative complications such as non-union and implant failure [4][5][6]. Although several studies had found that parallel plating can provide good clinical results and is biomechanical superior to orthogonal plating in osteoporotic fracture [1,22], it is associated with a greater extent of soft tissue dissection in the distal humerus [11,12] a higher HO formation rate [23,24], and greater difficulty in contouring and applying the lateral plates [19]. Posterior two-plate fixation is considered to be an alternative technique [17] that also has good functional outcomes, high union rates, and low complication rates in c-type DHFs [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, orthogonal plating is reported to have inadequate fixation in cases with osteoporotic and comminuted fractures, which may lead to fixation failure or non-unions [10]. Recently, parallel constructs had gained more surgical popularity for treating comminuted DHFs due to the superiority over orthogonal constructs based on recent biomechanical studies [8,[11][12][13] and a biomechanical meta-analysis [9]. However, the main disadvantage of the parallel fixation is the wide soft tissue dissection [9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evolution of surgical implants and techniques, AO/OTA type 13 C2 and C3 fractures of the distal humerus still pose a surgical challenge. Open reduction and internal fixation (ORIF) is often preferred as the first choice of treatment, but the results vary and are sometimes disappointing, especially in elderly patients [10,25,29]. The success of ORIF depends on correct reduction of the fracture, reconstruction of the articular surface, and the stability and rigidity of the fixation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Protocols involving extensive arthrolysis, radial head excision and temporary external fixation have been elaborated [22,23]. Due to the complexity of elbow injuries, optimal treatment of their sequelae varies among different centres according to the individual experience [23][24][25].…”
Section: Introductionmentioning
confidence: 99%